High temporal resolution transparent thermoelectric temperature sensors for photothermal effect sensing. Issue 1 (2nd November 2022) - Lee, Junhee; Hwang, Seongkwon; Hong, Nari; Kwak, Jeonghun; Jang, Jae Eun; Chung, Seungjun; Kang, Hongki
Abstract : We propose a high-speed transparent temperature sensor based on the thermoelectric effect of an inkjet-printed conductive polymer for direct monitoring of the photothermal effect in biomedical applications. Abstract : We propose inkjet-printed high-speed and transparent temperature sensors based on the thermoelectric effect for direct monitoring of the photothermal effect. They consist of highly transparent organic thermoelectric materials that allow excellent biocompatibility and sub-ms temporal resolution, simultaneously. Our transparent thermoelectric temperature sensors can be used to advance various photothermal biomedical applications.